Genetic and phenotypic determinants of morphologies in 3D cultures and xenografts of lung tumor cell lines. Issue 4 (12th January 2023) - Matsubara, Daisuke; Yoshimoto, Taichiro; Akolekar, Ninad; Totsuka, Takashi; Amano, Yusuke; Kihara, Atsushi; Miura, Tamaki; Isagawa, Yuriko; Sakuma, Yuji; Ishikawa, Shumpei; Ushiku, Tetsuo; Fukayama, Masashi; et al.
Abstract: We previously proposed the classification of lung adenocarcinoma into two groups: the bronchial epithelial phenotype (BE phenotype) with high‐level expressions of bronchial epithelial markers and actionable genetic abnormalities of tyrosine kinase receptors and the non‐BE phenotype with low‐level expressions of bronchial Bronchial epithelial (BE) epithelial markers and no actionable genetic abnormalities of tyrosine kinase receptors. Here, we performed a comprehensive analysis of tumor morphologies in 3D cultures and xenografts across a panel of lung cancer cell lines. First, we demonstrated that 40 lung cancer cell lines (23 BE and 17 non‐BE) can be classified into three groups based on morphologies in 3D cultures on Matrigel: round ( n = 31), stellate ( n = 5), and grape‐like ( n = 4). The latter two morphologies were significantly frequent in the non‐BE phenotype (1/23 BE, 8/17 non‐BE, p = 0.0014), and the stellate morphology was only found in the non‐BE phenotype. SMARCA4 mutations were significantly frequent in stellate‐shaped cells (4/4 stellate, 4/34 non‐stellate, p = 0.0001). Next, from the 40 cell lines, we successfully established 28 xenograft tumors (18 BE and 10 non‐BE) in NOD/SCID mice and classified histological patterns of the xenograft tumors into three groups: solid ( n = 20), small nests in desmoplasia ( n = 4), and acinar/papillary ( n = 4). The latter two patterns were characteristically found in the BE phenotype. The non‐BE phenotype exhibited a solid pattern with significantly less content of alpha‐SMA‐positive fibroblasts ( p = 0.0004) and collagen ( p = 0.0006) than the BE phenotype. Thus, the morphology of the tumors in 3D cultures and xenografts, including stroma genesis, reflects the intrinsic properties of the cancer cell lines. Furthermore, this study serves as an excellent resource for lung adenocarcinoma cell lines, with clinically relevant information on molecular and morphological characteristics and drug sensitivity. Abstract : Here, we focused on cell line morphology in 3D cultures and xenograft tumors. In the bronchial epithelial phenotype, most of the cell lines displayed a round morphology in 3D culture, and some of them showed acinar or papillary patterns and desmoplastic reactions in xenograft tumors. In contrast, the non‐bronchial epithelial phenotype cell lines frequently displayed stellate or grape‐like morphologies in 3D culture and showed solid patterns with no desmoplastic reactions in xenograft tumors. This study serves as an excellent resource for lung adenocarcinoma cell lines with clinically relevant information on molecular and morphological characteristics.